Traveler Biosecurity Behavior during the COVID-19 Pandemic: Effects of Intervention, Resilience, and Sustainable Development Goals. (September 2022) - Kim, Myung Ja; Bonn, Mark; Hall, C. Michael
Even prior to COVID-19, biosecurity was a significant issue for tourism, especially at national borders. Since personal nonpharmaceutical interventions can be effective for an individual's health and psychological resilience during a pandemic, understanding tourists' biosecurity behavior is essential given the broader relationship with traveling during COVID-19. However, existing research has not explicitly examined this relationship during any pandemic, nor has it explored potential long-term implications. To fill this gap, this study built and tested a theoretically comprehensive framework including prosocial behavior, ethics, perception, intervention, resilience, biosecurity behavior, and the Sustainable Development Goals (SDGs) due to COVID-19. Results reveal that prosocial behavior and perception have significant impacts on intervention, which influences resilience and biosecurity behavior. Resilience has an effect on biosecurity behavior. Three SDG groups have different effects on the relationship between intervention and biosecurity behavior. Deep learning sheds light on tourist's biosecurity practices during COVID-19 and when international travel resumes.